Over the Hedge : Exchange Rate Volatility, Commodity Price Correlations, and the Structure of Trade - Raddatz, Claudio (2012)
A long empirical literature has examined the idea that, in the absence of hedging mechanisms, currency risk should have an adverse effect on the export volumes of risk averse exporters. But there are no clear conclusions from this literature, and the current consensus seems to be that there is at most a weak negative effect of exchange rate volatility on aggregate trade flows. However, most of this literature examines the impact of exchange rate volatility on aggregate trade flows, implicitly assuming a uniform impact of this volatility on exporters across sectors. This paper explots the fact that, if exchange rate volatility is detrimental for trade, firms exporting goods that offer a natural hedge against exchange rate fluctuations -- i.e. those whose international price is negatively correlated with the nominal exchange rate of the country where they operate -- should be relatively benefited in environments of high exchange rate volatility, and capture a larger share of the country's export basket. This hypothesis is tested using detailed data on the composition of trade of 132 countries at 4-digit SITC level. The results show that the commodities that offer natural hedge capture a larger share of a country's export basket when the exchange rate is volatile, but there is only weak evidence that the availability of financial derivatives to hedge currency risk reduces the importance of a sector's natural hedge.